Immunogenic cell death: The cornerstone of oncolytic viro-immunotherapy - Palanivelu, Lalitha; Liu, Ching-Hsuan; Lin, Liang-Tzung (Frontiers in Immunology, 2023)
According to the World Health Organization, cancer is one of the leading global health concerns, causing nearly 10 million deaths in 2020. While classical chemotherapeutics produce strong cytotoxicity on cancer cells, they carry limitations of drug resistance and off-target effects and sometimes fail to elicit adequate antitumor protection against tumor relapse. Additionally, most cancer cells have developed various ways to escape immune surveillance. Nevertheless, novel anticancer strategies such as oncolytic viro-immunotherapy can trigger immunogenic cell death (ICD), which can quickly grasp the attention of the host defense machinery, resulting in an ensuing antitumor immune response. Specifically, oncolytic viruses (OVs) can infect and destroy targeted cancer cells and stimulate the immune system by exposing pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs) to promote inflammatory reactions, and concomitantly prime and induce antitumor immunity by the release of neoantigens from the damaged cancer cells. Thus, OVs can serve as a novel system to sensitize tumor cells for promising immunotherapies. This review discusses the concept of ICD in cancer, centralizing ICD-associated danger signals and their consequence in antitumor responses and ICD induced by OVs. We also shed light on the potential strategies to enhance the immunogenicity of OVs, including the use of genetically modified OVs and their combination with ICD-enhancing agents, which are helpful as forthcoming anticancer regimens.